2014
DOI: 10.4172/psychiatry.1000131
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Families Living with a Mentally Ill Family Member

Abstract: Objective: To explore the experiences, describe the strengths to cope, and formulate recommendations to support families living with a mentally ill family member in the Thabo-Mofutsanyana district of the Free State Province in South Africa. Method: A qualitative, phenomenological design, and in-depth interview guided by three central questions. A total of 14 interviews were conducted. Results: Three main themes that were identified after data analysis: positive experiences and strengths, negative experiences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…This finding is similar to the finding by Monyaluoe et al (2014) as well as Mokgothu et al (2015) who also found that families of mentally ill family members undergo a process of acceptance.…”
Section: The Families Explained Their Process Of Acceptancesupporting
confidence: 80%
See 2 more Smart Citations
“…This finding is similar to the finding by Monyaluoe et al (2014) as well as Mokgothu et al (2015) who also found that families of mentally ill family members undergo a process of acceptance.…”
Section: The Families Explained Their Process Of Acceptancesupporting
confidence: 80%
“…Similar results were found by Monyaluoe, Mokoena-Mvandaba, Du Plessis and Koen (2014), namely that families of mentally ill family members experience emotional pain, guilt and concern. h e a l t h s a g e s o n d h e i d 2 2 ( 2 0 1 7 ) 2 8 e3 5…”
Section: The Family Members Experienced Specific Initial Emotionssupporting
confidence: 78%
See 1 more Smart Citation
“…Practical examples of support go beyond cooking, household chores, assisting with keeping medical appointments and financial support, as emotional support is a crucial element in patient rehabilitation. Continued care and support for people with mental illness can be demanding and challenging, causing families to become frustrated, stranded, overburdened and exhausted (Monyaluoe, Mvandaba, Plessis, & Koen, 2014). South Africa is committed to the national imperative of provision of care, treatment and quality healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…The experiences of caregivers of people with mental health issue have been described in a significant body of research, mostly from western countries, [1][2][3] and to a smaller extent from low-resource countries. [3][4][5][6][7][8][9][10] Most studies focus on measuring the negative aspects of caregiving, called "family burden," which is usually defined as the influence of giving care to a person with mental health problem on the living situation of their caregiver and the emotional, psychological, physical, and economic consequences thereof (Awad,11 WHO 12(p12) ). A distinction is often made between "objective" and "subjective" burden.…”
Section: Introductionmentioning
confidence: 99%